Teaching Modeling - An Initial Classification of Related Issues - Kuzniarz, Ludwik; Börstler, Jürgen (Electronic Communications of the EASST, 2012)
Modeling is an important skill needed in both science and engineering domains. In software engineering, in particular, models are ubiquitous artefacts. The development, manipulation and understanding of models is therefore an important learning objective. The paper describes motivations and an outline of a research project aimed at classifying issues related to the teaching and learning of modeling together with some initial research results.